Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Implementation and validation of 2-D-array based tests in routine linac quality assurance - Valenta, Jiri; Schmidt, Manfred; Bert, Christoph (Zeitschrift für Medizinische Physik, 2024)
Purpose: In medical linac quality assurance (QA), to replace film dosimetry with low-resolution 2-D ionization chamber array measurements, to validate the procedures, and to perform a comprehensive sensitivity analysis. Methods: A 2-D ionization chamber array with a spatial resolution of 7.62 mm was deployed to perform the following tests: Junction tests, MLC transmission test, beam profile constancy vs. gantry angle test, beam profile constancy vs. low dose delivery test, and beam energy constancy vs. low dose delivery test. Test validation and sensitivity analyses based on short- and long-term statistics of the test results were performed. Results: All selected mechanical and dosimetry tests could be successfully performed with a 2-D array. Considering the tolerance limits recommended by the AAPM Task Group 142 report (2009), sensitivities of 99.0% or better and specificities ranging from 99.5% to 99.9% could be achieved in all tests when the proper metrics were chosen. Conclusions: The results showed that a low-resolution 2-D ionization chamber array could replace film dosimetry without having to sacrifice high test sensitivity. Its implementation in the routine clinical linac QA program may involve considerable QA time savings.
CRIS-Team Scopus Importer:2024-03-22
Keywords: 2-D array; Linear accelerator quality assurance; Test sensitivity; Test specificity

Individual Radiosensitivity in Lung Cancer Patients Assessed by G0 and Three Color Fluorescence in Situ Hybridization - Mayo, Theresa; Schuster, Barbara; Ellmann, Anna; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (OBM Genetics, 2019)
Background: It is well known that radiosensitivity varies substantially from individual to individual. This may influence the tumor response and also cause side effects in normal tissues following the radiotherapy treatment for cancers. Therefore, we aimed to analyze the sensitivity of a lung cancer cohort to see whether patients display similar radiosensitivity distribution as compared to healthy individuals. Methods: Blood samples of healthy individuals (n = 244) and a small group of lung cancer patients (n= 38) were irradiated ex vivo and chromosomes # 1, 2 and 4 were analyzed by the 3-color fluorescence in situ hybridization (FISH) technique. Additionally, the data from 400 individuals from previously published studies were also analyzed, which included a healthy cohort as well as rectal cancer patients. Chromosomal aberrations were counted and expressed as breaks per metaphase (B/M). The chromosomal aberrations in the control sample (background) were subtracted to obtain only the radiation-induced aberrations. Results: The lung cancer cohort had significantly increased background B/M values (p<0.001). Increased radiosensitivity was stated if the B/M value exceeded 0.55. The percentage of individuals with increased radiosensitivity was slightly higher in the patient groups compared to that in healthy individuals. Conclusions: Individualizing treatment by adjusting the radiation dose can help in reducing side effects, as cancer patients have a broader range of individual radiosensitivity.
CRIS-Team Scopus Importer:2024-12-16
Keywords: breaks per metaphase; chromosomal aberrations; individual radiosensitivity; lung cancer; rectal cancer; Three color fluorescence in situ hybridization

Influence of gender on radiosensitivity during radiochemotherapy of advanced rectal cancer - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Büttner-Herold, Maike; Weber, Klaus; Denz, Axel; Grützmann, Robert; Hartmann, Arndt; Geinitz, Hans; Fietkau, Rainer; et al. (Cancers, 2022)
Gender is increasingly recognized as an important factor in medicine, although it has long been neglected in medical research in many areas. We have studied the influence of gender in advanced rectal cancer with a special focus on radiosensitivity. For this purpose, we studied a cohort of 495 men (84.1% ≥ T3, 63.6% N1, 17.6%, M1) and 215 women (84.2% ≥ T3, 56.7% N1, 22.8%, M1) who all suffered from advanced rectal cancer and were treated with radiochemotherapy. The energy deposited, DNA double-strand break (dsb) repair, occurrence of chromosomal aberrations, duration of therapy, tumor regression and tumor-infiltrating lymphocytes, laboratory parameters, quality of life and survival were assessed. The residual DNA dsb damage 24 h after irradiation in lymphocytes was identical in both sexes. Furthermore, chromosomal aberrations accurately reflecting radiosensitivity, were similar in both sexes. There were no gender-dependent differences in tumor regression, tumor-infiltrating lymphocytes and outcome indicating no differences in the radiosensitivity of cancer cells. The irradiated tumor volume in women was slightly lower than in men, related to body weight, no difference was observed. However, when the total energy deposited was calculated and related to the body weight, women were exposed to higher amounts of ionizing radiation. During radiochemotherapy, decreases in blood lymphocyte counts and albumin and several quality-of-life parameters such as nausea and vomiting, loss of appetite, and diarrhea were significantly worse in women. There is no difference in radiation sensitivity between men and women in both normal tissue and tumors. During radiochemotherapy, the quality of life deteriorates more in women than in men. However, women also recover quickly and there are no long-term differences in quality of life.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Blood values; Deposited energy; DNA double-strand breaks; Gender; Quality of life; Radiochemotherapy; Radiosensitivity; Radiosensitivity; Rectal cancer

Influence of MRI Distortion Correction on the local Control of stereotactically irradiated Brain Metastases - Putz, Florian; Siavooshhaghighi, Hadi; Grigo, Johanna; Masitho, Siti; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manfred; Semrau, Sabine; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

In the Case of Radiochemotherapy of advanced Rectal Cancer, there is only slight gender-related Differences, none in terms of Radiation Sensitivity! - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Longitudinal Spread Analysis of Patients with Glioblastoma: high Prevalence of discontinuous Tumor Foci with no strong Relation to the Fibrous Tract System - Schmitter, Charlotte; Weissmann, Thomas; Mansoorian, Sina; Lettmaier, Sebastian; Semrau, Sabine; Schmidt, Manfred; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low- vs. high-dose radiotherapy in Graves’ ophthalmopathy: a retrospective comparison of long-term results - Weissmann, Thomas; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Bert, Christoph; Schmidt, Manfred; Kruse, Friedrich; Ott, Oliver; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Putz, Florian (Strahlentherapie und Onkologie, 2021)
Purpose: Radiotherapy represents an effective treatment option in Graves’ ophthalmopathy (GO), leading to palliation of clinical symptoms. However, there are only a limited number of trials comparing the effectiveness of low- vs. high-dose radiotherapy. Methods: We analyzed 127 patients treated with radiotherapy for stage 3/4 GO (NOSPECS classification). Patients were treated with single doses of 2.0 Gy (cumulative dose 20 Gy) until 2007, afterwards a single dose of 0.8 Gy (cumulative dose 4.8 Gy) was applied. With a median follow-up-time of 9.0 years, the treatment efficacy (overall improvement, sense of eye pressure, lid edema, ocular motility, exophthalmos, subjective vision, and diplopia) and adverse effects were analyzed by a standardized survey. Results: Overall, 63.8% described improvement of symptoms after radiotherapy. No significant differences in overall treatment response and improvement of main outcome measures between low- or high-dose radiotherapy treatments are detectable, while low-dose radiotherapy leads significantly more often to retreatment (13.1% vs. 1.7%, p = 0.016). The main independent predictor of treatment response is the presence of lid edema (odds ratio, OR, 3.53; p = 0.006). Conclusion: At long-term follow-up, the majority of patients reported palliation of symptoms with limited adverse effects, suggesting clinical effectiveness of radiotherapy for amelioration of GO symptoms independent of low- or high-dose radiotherapy.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Exophthalmos; Graves’ ophthalmopathy; Low dose radiation therapy; Radiotherapy; Thyroid eye disease

Magnetic Resonance thermometry images of hyperthermia treatments of sarcomas for prediction of therapy responses-need of data reprocessing and cleaning - Khatun, Rupali; Hader, Michael; Schmidt, Manfred; Bert, Christoph; Wadepohl, Martin; Fietkau, Rainer; Ott, Jessica; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Treatment planning facilitates clinical decision making for hyperthermia treatments - Kok, H. P.; van der Zee, J.; Guirado, F. Navarro; Bakker, A.; Datta, N. R.; Abdel-Rahman, S.; Schmidt, Manfred; Wust, P.; Crezee, J. (International Journal of Hyperthermia, 2021)
Background: Treatment quality is important in clinical hyperthermia. Guideline-based treatment protocols are used to determine system settings and treatment strategies to ensure effective tumor heating and prevent unwanted treatment-limiting normal tissue hot spots. Realizing both these goals can prove challenging using generic guideline-based and operator-dependent treatment strategies. Hyperthermia treatment planning (HTP) can be very useful to support treatment strategies. Although HTP is increasingly integrated into the standard clinical workflow, active clinical application is still limited to a small number of hyperthermia centers and should be further stimulated. Purpose: This paper aims to serve as a practical guide, demonstrating how HTP can be applied in clinical decision making for both superficial and locoregional hyperthermia treatments. HTP in clinical decision making: Seven problems that occur in daily clinical practice are described and we show how HTP can enhance insight to formulate an adequate treatment strategy. Examples use representative commercially available hyperthermia devices and cover all stages during the clinical workflow. Problems include selecting adequate phase settings, heating ability analysis, hot spot suppression, applicator selection, evaluation of target coverage and heating depth, and predicting possible thermal toxicity in case of an implant. Since we aim to promote a general use of HTP in daily practice, basic simulation strategies are used in these problems, avoiding a need for the application of dedicated advanced optimization routines that are not generally available. Conclusion: Even fairly basic HTP can facilitate clinical decision making, providing a meaningful and clinically relevant contribution to maintaining and improving treatment quality.
CRIS-Team Scopus Importer:2021-04-16
Keywords: clinical decision making; Hyperthermia; optimization; treatment planning; treatment quality; treatment strategy